2023
DOI: 10.1021/acsomega.3c00244
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Avermectin B2 Microcapsules and Effective Control of Root-Knot Nematodes

Abstract: Polyurethane microcapsules of avermectin B2 were prepared by means of interfacial polymerization with methylene diphenyl diisocyanate as the wall material and triethanolamine as the initiator. The microcapsules were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The surfaces of the microcapsules were found to be smooth and almost spherical, and the encapsulation efficiency was high. The avermectin B2 microcapsules exhibited a good diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These results confirm the superior control effect exhibited by the lambda-cyhalothrin microcapsules compared with the lambda-cyhalothrin EC at the same dosage. It showed that microcapsules can prolong the persistent period of insecticides and reduce the number of drugs, which provides a new direction for market development of pesticides. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm the superior control effect exhibited by the lambda-cyhalothrin microcapsules compared with the lambda-cyhalothrin EC at the same dosage. It showed that microcapsules can prolong the persistent period of insecticides and reduce the number of drugs, which provides a new direction for market development of pesticides. , …”
Section: Resultsmentioning
confidence: 99%
“…It showed that microcapsules can prolong the persistent period of insecticides and reduce the number of drugs, which provides a new direction for market development of pesticides. 21 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…Liu et al developed a novel crystallization device and investigated the effects of variable parameters on crystal size and crystal size distribution (CSD) of dolutegravir sodium . Furthermore, microfluidics has been reported to hold great potential for the production of monodisperse spherical particles and pesticide microcapsules. Despite the numerous advantages of microfluidic crystallization, research on microfluidics for oiling-out crystallization is still limited and remains an underexplored area.…”
Section: Introductionmentioning
confidence: 99%
“…The potato rot nematode, Ditylenchus destructor Thorne, is a soil parasite with strong ability to destroy roots of crops, such as sweet potato, potato, and Chinese medicinal plants, posing a serious threat to global food security. , As an example, the potato rot nematode causes a 20–30% reduction in crop yield, resulting in economic losses amounting to several billion dollars annually . Unfortunately, there are only a few chemicals that are effective against the nematode.…”
Section: Introductionmentioning
confidence: 99%